An Implementation of Ordinal Probit Regression Model on Factor Affecting East Java Human Development Index - Purnama, Mohammad Dian (Bina Nusantara University, 2024)
An instrument for measuring human development, the Human Development Index (HDI) looks at how well human development has been achieved in relation to a few fundamental aspects of quality of life. In 2023, East Java's HDI showed an increase in the last three years with the latest value of 73.38. Despite the increase, East Java still has the lowest HDI in Java and Bali. This situation suggests the need for an in-depth analysis of the factors that influence HDI. This study aims to identify factors that contribute to HDI to formulate more appropriate policies in the future. The data used is the HDI of East Java in 2023 with ordinal categories. To analyze the ordinal data, the ordinal probit regression method was applied. The results show that the percentage of poor people has a significant influence on HDI. In addition, the classification accuracy of the model is obtained with a value of 50.5%, which indicates that the accuracy of the model in predicting HDI into the right category reaches 50.5%.